Floristic composition of a Rain Forest fragment in the Serra da Jibóia, Santa Terezinha, Bahia, Brazil - Carvalho-Sobrinho, Jefferson G. de; Queiroz, Luciano P. de (SITIENTIBUS série Ciências Biológicas, 2005)
This paper presents a checklist of the phanerogamic flora of a Atlantic Rain Forest fragment in the Serra da Jibóia, municipality of Santa Terezinha, Bahia. The survey was based on collections previously made at the “Morro da Pioneira”, in the northern part of the mountain range, currently housed at the HUEFS herbarium. A total of 269 species belonging to 195 genera of 80 families of flowering plants are listed. The families with higher specific diversity were Leguminosae (29), Rubiaceae (16), Asteraceae (12), Melastomataceae (12), Orchidaceae (11), Myrtaceae (10), Solanaceae (10), Bromeliaceae (10), and Poaceae (9). Among canopy plants, the families most representative were Leguminosae (15), Myrtaceae (7), Melastomataceae (7), Solanaceae (6), Lauraceae (5), Annonaceae (4), Rubiaceae (4), Apocynaceae (3), and Clusiaceae (3). This survey illustrates the great floristic diversity and the presence of endemic and restricted distribution of Brazilian Atlantic Rain Forest species, characterizing this fragment as an important remainder of this biome in Bahia.